Cálculo y diseño de un modelo de molino de martillos para granos secos. - Montoya Chuncho, Claudia Cecilia (2021)
In the present titration work, the design of a hammer mill for dry grains is developed, specifically oriented to the crushing of dry corn to sizes that range between 1 to 3 mm, on average, which is the commercialization size of the corn destined for poultry feed or for use as an ingredient in the preparation of balanced feed. The methodological process developed to identify the basic parameters for the initial sizing of the hammer mill is detailed, based on the external forces that the machine must develop and the production requirements, and subsequently the scientific methods for the calculation, design and selection of the main electromechanical components. Following the calculations and selection of the main elements of the mill, the corresponding analysis of the calculated elements is carried out, which allow to derive the process, in the corresponding conclusions and recommendations. In the annexes the graphic designs of the mechanical elements of the mill are presented.